PENGARUH PERAN ORANG TUA PADA TERAPI WICARA TERHADAP KEMAMPUAN BICARA PADA ANAK PENDERITA AUTIS DI SDK STA. MARIA ASSUMPTA DAN PUSAT LAYANAN AUTIS NAIMATA KOTA KUPANG - Desliyane Rambu Leki (Universitas Citra Bangsa, 2019)
Autism is a developmental disorder that affects on verbal and non verbal communication disorders and social interactions. Parents have a very dominant role in healing efforts for children with special needs such as autism. The role of parents needed by children with autism during speech therapy. The purpose of this research is to know the influence of parent’s role in speech therapy on speech ability of children with autism in SDK Sta. Maria Asumpta And Autism Service Center Naimita, kota Kupang. This research uses analytic correlational research design with cross sectional approach in SDK Sta. Maria Asumpta And Autism Service Centre Naimata, Kota Kupang. The sample is selected by using total sampling technique and divided into 2 places, there are 10 respondents in SDK Sta. Maria Asumpta and 25 respondents in Autism Service Centre Naimita, kota Kupang. Data is collected by using questionnaire and observation sheet then done by using Spearman Rho test. The result of this research, from 35 respondents show p-value =0,002, So at the level of significance 5% (a=0.05), then p<0.05. The conclusion of this research is there is influence of parent’s role in speech therapy on speech ability of children with autism in SDK Sta. Maria Asumpta And Autism Service Center Naimita, kota Kupang. Based on the results of this study suggested that parents to improve the implementation of speech therapy in children with autism so that speech ability of children with autism be better. Keywords: The role of parents, speech therapy, Speech ability, Autism